Paternal Involvement in and Sociodemographic Correlates of Infant and Young Child Feeding in a District in Coastal South India: A Cross-Sectional Study - Mithra, Prasanna; Unnikrishnan, Bhaskaran; T, Rekha; Kumar, Nithin; Holla, Ramesh; Rathi, Priya (Frontiers in Public Health, 2021)
Context: The feeding practices during first two years of life determine the overall health and survival during childhood and beyond. Child nutrition is responsibility of both parents and so far emphasis has been laid mostly on mothers. Fathers’ involvement towards IYCF has been proved to be of paramount importance and yet it is given limited importance. Objectives: To study the level of paternal involvement towards IYCF & its associated factors and to assess the knowledge, attitude and practices towards IYCF in Dakshina Kannada District in South Indian State of Karnataka. Settings and Design: This community based cross sectional study was conducted in the coastal District of Dakshina Kannada; Karnataka State in India. Methods: The study included 450 fathers of infant and young children (aged < two years) in five taluks of Dakshina Kannada district. They were assessed for knowledge, attitude and practices related to IYCF. Median score for the practice component was considered as cut off to classify involvement in IYCF. Data were analyzed using IBM SPSS Statistics for Windows, Version 25.0. Armonk, NY: IBM Corp. Chi-square test and Binary Logistic Regression with Hosmer-Lemeshow goodness of fit model, were used. Un-adjusted and adjusted odds ratios were generated. A ‘p’ value of <0.05 was considered statistically significant. Results: Mean age of the study population was 34.6 years (SD: 5.4). The practice scores median (IQR) was 34.0 (IQR-31.0-39.0) and 40.9% of the participants had poor involvement in IYCF. This was significantly higher among fathers from predominantly urban area. Those who had education above graduation and younger fathers had better involvement in IYCF. Conclusions: Less than half of fathers had poor involvement in IYCF and it was lower among fathers from urban areas, higher age and lower educational levels.